Penerapan Pelaksanaan Program One Stop Service (OSS) Dalam Meningkatkan Manajemen Pelayanan Administrasi Publik di Kantor Camat Medan Tembung - Nurafni, Anggi; Imsar, Imsar; Aisyah, Siti (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the implementation of the One Stop Service (OSS) at the Medan Tembung District Office using a qualitative approach and NVIVO 15 analysis. Findings reveal that OSS remains semi-integrated, with major gaps in technology, human resources, processes, information, and organizational values. These hinder service integration and user orientation. The study concludes that OSS success depends not only on technology but also on institutional capacity, HR competence, and inter-agency coordination.